Group I permuted intron-exon (PIE) sequences self-splice to produce circular exons. - Puttaraju, M (1992)
Circularly permuted group I intron precursor RNAs, containing end-to-end fused exons which interrupt half-intron sequences, were generated and tested for self-splicing activity. An autocatalytic RNA can form when the primary order of essential intron sequence elements, splice sites, and exons are permuted in this manner. Covalent attachment of guanosine to the 5' half-intron product, and accurate exon ligation indicated that the mechanism and specificity of splicing were not altered. However, because the exons were fused and the order of the splice sites reversed, splicing released the fused-exon as a circle. With this arrangement of splice sites, circular exon production was a prediction of the group I splicing mechanism. Circular RNAs have properties that would make them attractive for certain studies of RNA structure and function. Reversal of splice site sequences in a context that allows splicing, such as those generated by circularly permuted group I introns, could be used to generate short defined sequences of circular RNA in vitro and perhaps in vivo.